INFORMATION TECHNOLOGY ADOPTION AMONG THE FACULTY OF CEBU STATE COLLEGE OF SCIENCE AND TECHNOLOGY MAIN CAMPUS CEBU CITY: PROPOSED GAP BRIDGING STRATEGIES - Himang, Melanie M; Himang, Celbert M (Journal of Agriculture and Technology Management, 2008)
This study assessed the information technology adoption among the faculty of Cebu State College of Science and Technology – Main Campus including the level of computer experience of the faculty, with regard to: language programming software; operating systems; tool applications; graphics software; communication software; authoring; instructional courseware and variety, profile of the early adopters and mainstream faculty of CSCST, information technology adoption as to: computer use; purchase patterns; access to technology; personal satisfaction; prior learning; and hours of use; perception of the respondents on the effect of IT to teaching and learning, motivators and barriers of integrating IT in teaching-learning. There were evidences to support that early adopters were different from the mainstream faculty members of the CSCST Main Campus in the level of computer experience, personal and information technology adoption profiles. Early adopters and mainstream faculty members differ in their perception on the effect of information technology to teaching and learning while they do not vary considerably in their perception on what factors that motivate or prevent information technology adoption in teaching and learning. Moreover, the two groups were found out to have different preferences on the methods of learning, getting support and accessing information technology innovation. Generally, findings of this study support with Rogers’ theory of diffusion of innovation and these findings corroborate with the previous studies conducted in the Philippines and in foreign schools. A Gap bridging strategy was proposed for the CSCST.